2019
DOI: 10.1186/s12879-019-4635-6
|View full text |Cite
|
Sign up to set email alerts
|

Meningitis gone viral: description of the echovirus wave 2013 in Germany

Abstract: BackgroundAseptic meningitis epidemics may pose various health care challenges.MethodsWe describe the German enterovirus meningitis epidemics in the university hospital centers of Düsseldorf, Cologne and Berlin between January 1st and December 31st, 2013 in order to scrutinize clinical differences from other aseptic meningitis cases.ResultsA total of 72 enterovirus (EV-positive) meningitis cases were detected in our multicenter cohort, corresponding to 5.8% of all EV-positive cases which were voluntarily repor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Echovirus meningitis outbreaks have been reported to occur worldwide every 3 to 5 years [ 38 , 39 , 40 ]. The most recent EV meningitis epidemics in Europe occurred in Germany (Echovirus 30), in northern European countries in 2013–2014 (Echovirus 4) and in 2018 (Echovirus 30) [ 11 , 41 , 42 ]. However, sequencing data from other studies have suggested that there are genetic exchanges between different isolates, and multiple genotypes could circulate simultaneously in the same outbreak [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Echovirus meningitis outbreaks have been reported to occur worldwide every 3 to 5 years [ 38 , 39 , 40 ]. The most recent EV meningitis epidemics in Europe occurred in Germany (Echovirus 30), in northern European countries in 2013–2014 (Echovirus 4) and in 2018 (Echovirus 30) [ 11 , 41 , 42 ]. However, sequencing data from other studies have suggested that there are genetic exchanges between different isolates, and multiple genotypes could circulate simultaneously in the same outbreak [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Single or multiplex PCR platforms including EV detection increased the diagnostic yield and our knowledge regarding enteroviral involvement in pediatric central nervous system (CNS) infections [ 7 , 8 , 9 ]. Further characterization of EV species with molecular sequence data, comparative genomics and phylogenetic analysis is important to identify the circulating and emerging EVs causing CNS infection or neurologic manifestations and elucidate epidemic outbreaks on time [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analyses of the VP1 gene, as conducted in the present study, have been widely used for typing EVs and in molecular epidemiological investigations. Some EV serotypes (e.g., E6, E11, E18, E30 and CVB5) are still causing global epidemic outbreaks, while others (e.g., CVA9, E5 and E20) are primarily associated with endemic infections [ 18 , 41 45 ]. E18 has caused many aseptic meningitis outbreaks in Germany, the United States, Japan, Korea, and other countries or regions [ 44 , 46 – 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Influenza virus types A and B are responsible for more than half of all community-acquired viral pneumonia cases, particularly during influenza outbreaks ( Davis et al, 2014 ). Moreover, enteroviruses account for occasional respiratory illnesses during the summer months ( Graf et al, 2019 ). Interestingly, in 2020 and 2021, the stringent public health measures imposed to control the COVID-19 pandemic have suppressed most seasonal respiratory viruses; the notable exception is human rhinovirus/enterovirus ( Champredon et al, 2021 ; Rodgers et al, 2021 ).…”
Section: Respiratory Viruses and Other Viruses Causing Respiratory Dy...mentioning
confidence: 99%